Anaerobic decolorization and detoxification of cationic red X-GRL by Shewanella oneidensis MR-1. Issue 18 (17th September 2018) - Li, Qian; Feng, Xiao-Li; Li, Ting-Ting; Lu, Xue-Rong; Liu, Qiu-Yue; Han, Xue; Feng, Yu-Jie; Liu, Zhao-Ying; Zhang, Xi-Jia; Xiao, Xiang
ABSTRACT: The ability of an electrochemically active bacterium, Shewanella oneidensis MR-1, to decolorize azo dye cationic red X-GRL (X-GRL) was investigated. S. oneidensis MR-1 showed a high decolorization capability for X-GRL under anaerobic conditions. The Mtr respiratory pathway was proved to be involved in the extracellular decolorization of X-GRL. The decolorization efficiency of S. oneidensis MR-1 was significantly inhibited when the initial X-GRL concentration was over 200 mg L −1 . Increasing the inoculum volume of S. oneidensis MR-1 could obviously promote the X-GRL decolorization. The 100 mg L −1 X-GRL and 6% (v/v) inoculum volume were chosen as the optimal parameter. Under such a condition, almost all of X-GRL (100 mg L −1 ) could be completely reduced after 12-h incubation at the pH range of 5.5–8.0 and temperature range of 30–40°C. Salinity in the medium also affected X-GRL decolorization. Lactate and citric acid were found to be the suitable electron donors for X-GRL decolorization. Although the genotoxicity increased slightly, the phytotoxicity of X-GRL in the decolorization process was significantly reduced by S. oneidensis MR-1.